MODERATE ISLAM IN THOUGHT IBNU RUSYD - Jamaluddin, Jamaluddin; Muis, Andi Abd.; Putri, Nurwidya; Rosma, Rosma; Fauziah, Fauziah; Suhdi, Sulaiman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research discusses the attitude of moderation in fighting radicalism movements, especially in Indonesia. Why is this research interesting to discuss? Radicalism movements must be stemmed by education and understanding of the diversity of religious understandings in Indonesia. Therefore, the author offers Ibn Rushd's thoughts and personality as a famous philosopher. In historical records, Ibnu Rushd was a scholar who never attacked personally and accused his opponents of deviations in religious understanding. The moderation attitude shown by Ibnu Rushd can be used as an example in forming the character of Muslims in Indonesia. In terms of methodology, this article is a type of library research. Next, the author explores data from Ibn Rushd's books and uses a philosophical approach with content analysis. According to Ibnu Rushd, a scholar must have some essential personality traits of moderation. There are three parts: before, in, and after thinking. Before thinking, a scholar must have a personality that is open, honest, curious, skeptical, brave and patient. The ulama's personality in thinking is speculative, willing to be guided by experience and reason, willing to accept, ready to face mistakes and brave in making decisions. Furthermore, his personality after thinking about it was a tolerant and forgiving person